A comparative study of geosynthetically reinforced earth foundations in multi-utility transportation infrastructure for high-speed railways - Mandhaniya, Pranjal; Soni, Anish Kumar; Choudhary, Kirti; Ansari, Abdullah (Frontiers in Built Environment, 2023)
A high-quality railway track resting on an excellent foundation is required to support high-speed railway transportation. The foundations of high-speed railway tracks are generally constructed on the lifted embankment with the improved ground using different reinforcement agents like geosynthetics and rigid lateral support. The present study performed dynamic finite element simulations on a ballasted rail track laid over a geosynthetically reinforced embankment with and without facing wall support. Three foundation geometries were analyzed to examine the effect of facing wall support and geosynthetics on the lateral resistance of the foundation. An area loaded